Protecting vulnerable consumers in "switching markets" - Walter Beckert; Paolo Siciliani (Institute for Fiscal Studies (IFS), 2018)
This paper studies regulatory policy interventions aimed at protecting vulnerable consumers who are disengaged and thus exposed to exploitation. We model heterogeneous consumer switching costs alongside asymmetric market shares. This setting encompasses many markets in which established rms are challenged by new entrants. We identify circumstances under which such interventions can be counterproductive, both with regard to the stated consumer protection objective and the complementary aim to promote competition.
Keywords: L11; L13; D4; 330; switching costs; price discrimination; uniform pricing; most-favoured customer clauses; price regulation; competition